Statins do not inhibit the FGFR signaling in chondrocytes - Fafilek, B; Hampl, M; Ricankova, N; Vesela, I; Balek, L; Kunova Bosakova, M; Gudernova, I; Varecha, M; Buchtova, M; Krejci, P (Osteoarthritis and cartilage, 2017)
OBJECTIVE: Statins are widely used drugs for cholesterol lowering, which were recently found to counteract the effects of aberrant fibroblast growth factor receptor (FGFR3) signaling in cell and animal models of FGFR3-related chondrodysplasia. This opened an intriguing therapeutic possibility for human dwarfing conditions caused by gain-of-function mutations in FGFR3, although the mechanism of statin action on FGFR3 remains unclear. Here, we determine the effect of statins on FGFR signaling in chondrocytes. DESIGN: Cultured chondrocyte cell lines, mouse embryonic tibia cultures and limb bud micromasses were treated with FGF2 to activate FGFR signaling. The effects of atorvastatin, fluvastatin, lovastatin and pravastatin on FGFR3 protein stability and on FGFR-mediated chondrocyte growth-arrest, loss of extracellular matrix (ECM), induction of premature senescence and hypertrophic differentiation were evaluated. RESULTS: Statins did not alter the level of FGFR3 protein expression nor produce any effect on FGFR-mediated inhibition of chondrocyte proliferation and hypertrophic differentiation in cultured chondrocyte cell lines, mouse tibia cultures or limb bud micromasses. CONCLUSION: We conclude that statins do not inhibit the FGFR signaling in chondrocytes. Therefore the statin-mediated rescue of FGFR3-related chondrodysplasia, described before, is likely not intrinsic to the growth plate cartilage.
Keywords: kultivované buňky; Cell Line; signální transdukce; Chondrocytes; Rats; Cell Differentiation; chondrogeneze; Tibia; FGF signaling; tibie; Tissue Culture Techniques; Signal Transduction; Mice; Achondroplasia; chondrocyty; krysa rodu Rattus; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Cells, Cultured; zvířata; Chondrogenesis; Humans; statiny; techniky tkáňových kultur; Receptor, Fibroblast Growth Factor, Type 3; myši; Limb Buds; buněčné linie; buněčná diferenciace; Statins; receptor fibroblastových růstových faktorů, typ 3; lidé; končetinové pupeny; Animals